Thorstein Veblen, Joan Robinson, and George Stigler (probably) never met: Social preferences, monopsony, and government intervention - Laszlo Goerke; Michael Neugart (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2020)
Wages and employment are too low in a monopsony. Furthermore, a minimum wage or a subsidy may raise employment up to its first-best level. First, we analyze whether these important predictions still hold if workers compare their income to that of a refer- ence group. Second, we show that the undistorted, competitive outcome may no longer constitute the benchmark for welfare comparisons. Third, we derive a condition which guarantees that the monopsony distortion is exactly balanced by the impact of social comparisons. Finally, we show how wage restrictions and subsidies or taxes can be used to ensure this condition both for a welfarist and a paternalistic welfare objective.
Keywords: D10; H21; J30; J42; 330; social preferences; government intervention; minimum wage; monopsony; taxation; wage regulation